Translating pronominal causative constructions: Se faire vs. hacerse/fazer-se + Inf - Araújo, Sílvia (2013)
This paper presents a corpus-based study of pronominal causative constructions in a French-Spanish-Portuguese perspective. The combination of monolingual and multilingual corpus searches will help determine, at an initial phase, the conditions that underlie the functioning of se faire/hacerse/fazer-se in each language and, subsequently, the linguistic obstacles that hinder the literal translation of se faire into Spanish and Portuguese. Finally, a categorisation of the different translations of se faire will be offered. With this kind of study we aim to demonstrate the relevance of corpora as solid foundations for the creation of resources and methods for translation teaching and the training of translators.